2017
DOI: 10.3390/environments4040077
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Willingness to Pay for Improved Waste Collection Service in Gorkha Municipality of Nepal

Abstract: Municipal solid waste management is a growing problem in urban areas of Nepal where municipalities are severely constrained by budget to manage it effectively. Collecting fees from the public can aid finance for improving waste management service. This study evaluates willingness to pay (WTP) by 401 households, selected using a stratified sampling method from all 15 wards of Gorkha municipality of Nepal for improved waste collection service and the factors influencing it. We employed a contingent valuation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
32
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 12 publications
13
32
2
1
Order By: Relevance
“…So, these households were possibly disposing their waste indiscriminately. On the contrary, studies carried out in Nepal, Nigeria, India, and Ethiopia showed that urban households were willing to pay more for proper waste management [32][33][34][35][36]. Indeed, urban residents in Nepal, Nigeria, and Ethiopia where urban residents were paying 0.74, 2, and 1.07 USDs, respectively, for waste collection [33,34,36].…”
Section: Discussionmentioning
confidence: 98%
“…So, these households were possibly disposing their waste indiscriminately. On the contrary, studies carried out in Nepal, Nigeria, India, and Ethiopia showed that urban households were willing to pay more for proper waste management [32][33][34][35][36]. Indeed, urban residents in Nepal, Nigeria, and Ethiopia where urban residents were paying 0.74, 2, and 1.07 USDs, respectively, for waste collection [33,34,36].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, an increase in household"s income does not necessarily increase the WTP for a better waste management service. This is contrary to economics theory which postulates that higher income households have a greater demand for waste management and are more willing to pay for it (Hagos et al, 2012;Maskey and Singh, 2017). The coefficient of the variable type of employment is negative and significant with WTP.…”
Section: Factors Determining Willingness To Paymentioning
confidence: 68%
“…The coefficient of household income is negative and significant; implying that increase in household"s income does not necessarily increase the amount residents are WTP for a better waste management service. This is contrary to economics theory which postulates that higher income households have a greater demand for waste management and are more willing to pay for it (Hagos et al, 2012;Maskey and Singh, 2017).…”
Section: Determinants Of the Amount Of Money Householdsmentioning
confidence: 75%
See 1 more Smart Citation
“…It is crucial for the society to have positive willingness and participation towards SWM practices [17]. In the study investigated by a researcher, mentioned that SWM could be influenced if the willingness to pay by the people is not managed properly [18]. Similarly, they stated that accessibility of the location need to be focused on in order to provide good SWM services.…”
Section: Attitudes Perception and Willingness Toward Solid Wastementioning
confidence: 99%